Perbanyakan Tanaman Bambu (Bambusa sp.) dengan Teknik Kultur Jaringan Menggunakan Benzyl Amino Purine (BAP) di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Najwa Salsabila; Violita Violita; Mika Lestaria (Lembaga Yasin AlSys, 2026)
Bamboo plants (Bambusa sp.) have high economic and ecological value; however, conventional propagation still faces limitations in producing uniform, high-quality, and disease-free seedlings. This activity aimed to study the stages of bamboo tissue culture, including the preparation of MS medium, explant sterilization, inoculation, incubation, subculture, and acclimatization. The internship activity was carried out from January to February 2026 at the UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat. Data were obtained through observations of the bamboo tissue culture process at each stage and were then analyzed descriptively based on the success of explant growth and the constraints that emerged during the culture process. The results of the activity showed that some explants grew successfully, whereas others experienced browning and contamination. The success of bamboo tissue culture was influenced by the accuracy of sterilization, medium composition, the use of plant growth regulators, and incubation conditions. The conclusion of this activity affirms that tissue culture techniques have the potential to become an effective alternative for mass propagation and conservation of bamboo germplasm. Its implications indicate that the optimization of sterilization procedures, medium formulation, and culture condition regulation needs to be carried out continuously to improve the success of in vitro bamboo propagation.